Meningkatkan Pembelajaran Mandiri dengan ArtificiaI Intelligence dalam Era Digitalisasi Pendidikan di SMKN 9 Medan - Usman, Ari; Fitri Annisah lubis, Yessi; Lestari, Yuyun Dwi; Sarudin, Sarudin; Budiman, Arief (Jurnal Pengabdian Masyarakat, 2024)
Rapid technological developments, AI offers innovative solutions to support the teaching and learning process, allowing students to learn independently and adaptively according to their individual needs. Community service activities utilizing artificial intelligence to improve independent learning have proven their effectiveness in improving the quality of education. Through an interactive approach, participants are invited to understand the basic concepts of AI and its applications in the context of education, such as creating teaching materials, quizzes, and learning evaluations. This activity not only aims to increase knowledge about AI, but also to develop students' skills in using the technology wisely. With this activity, students can be more independent in their learning process and are ready to face challenges in the era of digitalization of education. This activity also provides recommendations for improving infrastructure and ongoing training for students and educators so that the use of AI can be more optimal in the future. The results of this activity show that students at SMKN 9 Medan have known and utilized AI in their learning activities with a high level of satisfaction.